Tolerance issues in museum educator’s activity - Pawlak, Magdalena (Granice tolerancji w sztuce i w wychowaniu, 2020)
The aim of the article is to show the complexity of museum educator’s roles. Nowadays they are not only required to have expert knowledge but also a range of other skills – including interpersonal ones. Educator meets the audience and must be open to their needs. In the majority of museums the most frequent visiting groups are school field trips – represented by the teacher. It is the educator–teacher relationship that requires tolerance and dialog. Evidently teachers and educators differ in many areas ranging from intended goals of the visit to their own competences. Examples shown in this article reveal recurring problems and prejudices.